El uso de benzocaína e hipotermia como sedantes para el transporte de juveniles de pez blanco, Chirostoma estor estor, Jordan 1879 - Sánchez Blanco, Judith (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
The effect of the use of benzocaine and hypothermia and its combination as sedatives in juveniles of C. estor estor were evaluated. Eleven different concentrations of benzocaine were used: 3, 6, 9, 12, 15, 18, 21, 24, 27, 30 and 40 mg / L; Establishing eleven treatments, with three replicates each and its control without anesthetic, in water with a salinity of 5 ‰. Observations were made in the following time period: 1, 2, 4, 8, 16, 32 and 64 minutes for each treatment. The hypothermia experiment was started at the ambient temperature of the water (23.8 ± 2.8 ° C) and then with reductions at 3 ° C intervals with the following relation: 21, 18, 15, 12 and 9 ° C; Establishing in total five treatments with three replicates each and its control at room temperature.

Se evaluó el efecto del uso de la benzocaína e hipotermia y su combinación como sedantes en juveniles de C. estor estor. Se utilizaron once distintas concentraciones de benzocaína: 3, 6, 9, 12, 15, 18, 21, 24, 27, 30 y 40 mg/L; estableciéndose once tratamientos, con tres réplicas cada uno y su testigo sin anestésico, en agua con una salinidad de 5‰. Se realizaron observaciones en el siguiente periodo de tiempo: 1, 2, 4, 8, 16, 32 y 64 minutos para cada tratamiento. El experimento de hipotermia se inició a la temperatura ambiente del agua (23.8±2.8°C) y posteriormente con reducciones a intervalos de 3°C con la siguiente relación: 21, 18, 15, 12 y 9°C; estableciéndose en total cinco tratamientos con tres réplicas cada uno y su testigo a temperatura ambiental.
Instituto de Investigaciones sobre los Recursos Naturales. Maestría en Ciencias en Limnología y Acuicultura
Keywords: info:eu-repo/classification/cti/2; INIRENA-M-2006-0002; Chiristoma estor estor; Benzocaína; Aloe vera; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5768